Semeryn Khr. Mythological and Archetypal Representation of Jewish Image in Katria Grynevuchewa’s Short Stories - Semeryn K. D. (Philological Treatises, 2020)
There the mythological and archetypical representation of the Jewish in short prose of Katria Grynevychewa collected in the cycles “On the Road to Shechem” and “The Unconquered,” is analyzed. It is revealed the writer portrays the Jewish as Exotic and Oriental, which is the result of mixing of interculultural experiences because of its ignorance) and as the realistic Jewish. It is emphasized that the rare realities of the coexistence of Ukrainians with Jews during the war (“The Unconquered”) bear a negative connotation due to the influence of stereotypes and the difficult social situation. The reception of evangelical events reflects the imperial-colonial cut of society, where the imperial Roman and the Jewish colonial are depicted lapidary. The Jewish Image contains numerous codes, therefore, floristic and zoomorphic images, as well as artistic phenomena, socio-political realities, religious and cultural objects, and traditions contribute to the formation of the multidimensional prospect of the Jewish. As the result of the research, the author states that the Jewish often appears as a mirror in which the Own, that is Ukrainian, is displayed in the Katria Grynevychewa’s texts.